Pengaruh Brand Image dan Company Reputation Terhadap Customer Loyalty dengan Customer Value sebagai Variabel Intervening (Studi Kasus Customer Sepeda Motor Honda di Provinsi Daerah Istimewa Yogyakarta) - Mahardhika, Chairul Dwi; Ningrum, Nonik Kusuma; Hatmanti, Lusia Tria (Universitas Batanghari Jambi, 2024)
This research aims to examine the influence of brand image and company reputation on customer loyalty with customer value as an intervening variable for branded motorbike customers. The research method is quantitative and has a population of people who use Honda brand motorbikes, with a sample of 102 respondents. Furthermore, the analysis technique implements multiple linear regression analysis. The test results showed that (1) no significant positive influence was found between brand image and customer value; (2) there is a significant positive influence between company reputation on customer value; (3) no significant positive influence was found between brand image on customer loyalty; (4) there is a significant positive influence between company reputation on customer loyalty; and (5) there is a significant positive influence between customer value and customer loyalty.